Use of performance-enhancing drugs and the Internet. Criminological reflections on a culture of communication in sport - Dresen, A.; Kläber, M.; Dietz, P. (Sportwissenschaft, 2014)
The use of physical performance-enhancing drugs is not limited to professional sports only, but has also been reported as common practice in recreational sports. A significant amount of epidemiological studies have highlighted the collective of fitness center visitors to be a high-risk group for using performance-enhancing drugs. From a sociological perspective, however, the decision to use performance-enhancing drugs (e.g., doping in the context of high-performance sport) is not an individual phenomenon only, but rather a result of social opportunity structures. This research article gives insight into enhancing-related Internet forums, in which the expertise of using and applying substances is passed on step by step. Using selected criminological learning theories, the "doping talk" in these social networks is hermeneutically reanalyzed and the Internet is exposed as a previously under-analyzed option for acquiring knowledge on the use of performance- enhancing drugs. This article shows that users of "doping platforms" are highly informed about doping and this offer of information acts like a knock-on effect to athletes who have so far abstained from doping. Consequently, future prevention models against the abuse of performance-enhancing drugs should consider the subcultural background of the milieu in which the athletes act.